PELATIHAN PERLINDUNGAN ANAK TERPADU BERBASIS MASYARAKAT (PATBM) UNTUK MEWUJUDKAN DESA LAYAK ANAK DI DESA MUNCUNG KECAMATAN KRONJO KABUPATEN TANGERANG: PELATIHAN PERLINDUNGAN ANAK TERPADU BERBASIS MASYARAKAT (PATBM) UNTUK MEWUJUDKAN DESA LAYAK ANAK DI DESA MUNCUNG KECAMATAN KRONJO KABUPATEN TANGERANG - Nikki Prafitri (PARADIGMA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community-Based Integrated Child Protection (PATBM) was formed to prevent cases of violence against children. The aim of the PATBM training is to create a child-friendly village, increase the knowledge of the management about PATBM and socialize the fulfillment of children's rights in Muncung Village, Kronjo District, Tangerang Regency. The method used in this service activity is education, question and answer and discussion. The target of this activity is the PATBM board, Government of Muncung Village, Posyandu cadres and community leaders. Activities are carried out by conveying material on the importance of PATBM, main tasks and functions of PATBM, PATBM policies to workflow. This training is expected to reactivate PATBM administrators in Muncung Village, increase administrators' understanding of PATBM and children's rights, encourage cooperation and collaboration between stakeholders to optimize PATBM, restructure inactive PATBM administrators and encourage monitoring and evaluation for PATBM in Mung Village.